Exploitation of lignocellulosic-based biomass biorefinery: A critical review of renewable bioresource, sustainability and economic views - Chen, Zhonghao; Chen, Lin; Khoo, Kuan Shiong; Gupta, Vijai Kumar; Sharma, Minaxi; Show, Pau Loke; Yap, Pow-Seng (Biotechnology advances, 2023)
Urbanization has driven the demand for fossil fuels, however, the overly exploited resource has caused severe damage on environmental pollution. Biorefining using abundant lignocellulosic biomass is an emerging strategy to replace traditional fossil fuels. Value-added lignin biomass reduces the waste pollution in the environment and provides a green path of conversion to obtain renewable resources. The technology is designed to produce biofuels, biomaterials and value-added products from lignocellulosic biomass. In the biorefinery process, the pretreatment step is required to reduce the recalcitrant structure of lignocellulose biomass and improve the enzymatic digestion. There is still a gap in the full and deep understanding of the biorefinery process including the pretreatment process, thus it is necessary to provide optimized and adapted biorefinery solutions to cope with the conversion process in different biorefineries to further provide efficiency in industrial applications. Current research progress on value-added applications of lignocellulosic biomass still stagnates at the biofuel phase, and there is a lack of comprehensive discussion of emerging potential applications. This review article explores the advantages, disadvantages and properties of pretreatment methods including physical, chemical, physico-chemical and biological pretreatment methods. Value-added bioproducts produced from lignocellulosic biomass were comprehensively evaluated in terms of encompassing biochemical products , cosmetics, pharmaceuticals, potent functional materials from cellulose and lignin, waste management alternatives, multifunctional carbon materials and eco-friendly products. This review article critically identifies research-related to sustainability of lignocellulosic biomass to promote the development of green chemistry and to facilitate the refinement of high-value, environmentally-friendly materials. In addition, to align commercialized practice of lignocellulosic biomass application towards the 21st century, this paper provides a comprehensive analysis of lignocellulosic biomass biorefining and the utilization of biorefinery green technologies is further analyzed as being considered sustainable, including having potential benefits in terms of environmental, economic and social impacts. This facilitates sustainability options for biorefinery processes by providing policy makers with intuitive evaluation and guidance.Urbanization has driven the demand for fossil fuels, however, the overly exploited resource has caused severe damage on environmental pollution. Biorefining using abundant lignocellulosic biomass is an emerging strategy to replace traditional fossil fuels. Value-added lignin biomass reduces the waste pollution in the environment and provides a green path of conversion to obtain renewable resources. The technology is designed to produce biofuels, biomaterials and value-added products from lignocellulosic biomass. In the biorefinery process, the pretreatment step is required to reduce the recalcitrant structure of lignocellulose biomass and improve the enzymatic digestion. There is still a gap in the full and deep understanding of the biorefinery process including the pretreatment process, thus it is necessary to provide optimized and adapted biorefinery solutions to cope with the conversion process in different biorefineries to further provide efficiency in industrial applications. Current research progress on value-added applications of lignocellulosic biomass still stagnates at the biofuel phase, and there is a lack of comprehensive discussion of emerging potential applications. This review article explores the advantages, disadvantages and properties of pretreatment methods including physical, chemical, physico-chemical and biological pretreatment methods. Value-added bioproducts produced from lignocellulosic biomass were comprehensively evaluated in terms of encompassing biochemical products , cosmetics, pharmaceuticals, potent functional materials from cellulose and lignin, waste management alternatives, multifunctional carbon materials and eco-friendly products. This review article critically identifies research-related to sustainability of lignocellulosic biomass to promote the development of green chemistry and to facilitate the refinement of high-value, environmentally-friendly materials. In addition, to align commercialized practice of lignocellulosic biomass application towards the 21st century, this paper provides a comprehensive analysis of lignocellulosic biomass biorefining and the utilization of biorefinery green technologies is further analyzed as being considered sustainable, including having potential benefits in terms of environmental, economic and social impacts. This facilitates sustainability options for biorefinery processes by providing policy makers with intuitive evaluation and guidance.